Biology and Ecosystem Conservation: The Role of Life Sciences in Addressing the Destruction of Nature - Efendi, Harja (Scientica Education Journal, 2025)
This study aims to examine the role of biology in ecosystem conservation and efforts to overcome environmental degradation through an evidence-based scientific approach. The method used is the Systematic Literature Review (SLR), which allows a comprehensive analysis of various relevant previous articles and studies. Literature was collected from leading academic databases, such as Google Scholar, PubMed, ScienceDirect, and JSTOR, with a focus on publications in the last five years that discuss ecosystem conservation, environmental restoration, and the use of biology in environmental conservation. The main keywords used in the search include "biological conservation," "ecosystem restoration," "environmental degradation," and "sustainable ecosystems." The results of the study indicate that biology has a crucial role in ecosystem conservation through a deep understanding of species, ecological interactions, and environmental dynamics. Effective conservation efforts require a holistic approach that integrates science, technology, and active community participation. Thus, to achieve environmental sustainability and reduce the impact of environmental degradation, a collaborative strategy is needed that makes biology the main pillar in ecosystem conservation and restoration efforts.